Entomology as I think.................... - Chakravathy, Dr. A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Entomology is systematic and scientific study of insects including basic and applied aspects. Basic aspects include laiect taxonomy, physiology, morphology, hio-ecology, anatomy and habitat distribution. Applied aspects include harmfid and beneficial insects, their role inn agriculture, horti-silvicultural and Ibrest ecosystems and impact of insects on human health. My contribution to Entomology is in the areas of host plant resistance in pulses and oilseeds to pod borers, cotton bollworms, sugarcane .borers, cardamom borer and rice gall midge, Vertebrate pest management practices in cropping systems in coastal and hill zones of Karanataka and Insect physiology and molecular biology. 1 am actively associated with the publication and editorial of several journals especially Insect Environment, Current Biotica, Newsletter for Bird Watchers, Uttar Pradesh Zoological Society and others.